Social Policies, Gender and Youth: Disputes over the Possibilities to Nominate, Signify and Do - Cena, Rebeca; Brunis, Lucrecia (Última Década, 2023)
This article analyzes social policies with an educational and labor component, aimed at young people in the province of Córdoba, Argentina between 2020-2021, from a gender perspective. In this case, gender appears as a category of analysis that allows us to account for the complexity of ways of “being young” and thus recognize different views and perspectives. The results show that social policies appear gendered and include some aspects of positive discrimination but do not adopt a transversal perspective that redistributes the exercise of power in relation to gender.